Striking the balance: ethical challenges and social implications of AI-induced power shifts in healthcare organizations. - Hähnel, Martin; Pfeiffer, Sabine; Graßmann, Stephan (AI and Society, 2024)
The emergence of new digital technologies in modern work organizations is also changing the way employees and employers communicate, design work processes and responsibilities, and delegate. This paper takes an interdisciplinary—namely sociological and philosophical—perspective on the use of AI in healthcare work organizations. Using this example, structural power relations in modern work organizations are frst examined from a sociological perspective, and it is shown how these structural power relations, decision-making processes, and areas of responsibility shift when AI is used. In the subsequent ethical part, opportunities for a fairer organization of work, but also dangers due to possibly changed power relations are elaborated and evaluated by presenting a realistic scenario from everyday clinical practice. After combining a proceduralist account of organizational ethics with a virtue-ethical approach, it is argued that certain organizational and character dispositions are necessary for employers and employees to meet the challenge of changing structural power relations in the future. With the same goal, a summative sociological perspective discusses challenges to workplace co-determination.<br
Keywords: Artifcial intelligence; Healthcare work organizations; Structural power relations; Organizational ethics; Procedural justice; Virtue ethics